Arterial cerebral blood volume–weighted functional MRI using pseudocontinuous arterial spin tagging (AVAST). Issue 3 (18th April 2014) - Jahanian, Hesamoddin; Peltier, Scott; Noll, Douglas C.; Hernandez Garcia, Luis
<x xml:space="preserve">Abstract</x> Purpose Neurovascular regulation, including responses to neural activation that give rise to the blood oxygenation level–dependent (BOLD) effect, occurs mainly at the arterial and arteriolar level. The purpose of this study is to develop a framework for fast imaging of arterial cerebral blood volume (aCBV) signal suitable for functional imaging studies. Methods A variant of the pseudocontinuous arterial spin tagging technique was developed in order to achieve a contrast that depends on aCBV with little contamination from perfusion signal by taking advantage of the kinetics of the tag through the vasculature. This technique tailors the tagging duration and repetition time for each subject. The proposed technique, called AVAST, is compared empirically with BOLD imaging and standard (perfusion‐weighted) arterial spin labeling (ASL) technique, in a motor‐visual activation paradigm. Results The average Z‐scores in the activated area obtained over all the subjects were 4.25, 5.52, and 7.87 for standard ASL, AVAST, and BOLD techniques, respectively. The aCBV contrast obtained from AVAST provided 80% higher average signal‐to‐noise ratio and 95% higher average contrast‐to‐noise ratio compared with that of the standard ASL measurements. Conclusion AVAST exhibits improved activation detection sensitivity and temporal resolution over the standard ASL technique, in functional MRI experiments, while preserving its quantitative nature and statistical advantages. AVAST particularly could be useful in clinical studies of pathological conditions, longitudinal studies of cognitive function, and studies requiring sustained periods of the condition. Magn Reson Med 73:1053–1064, 2015. © 2014 Wiley Periodicals, Inc.